New design criterion for walking vibrations - Allen, D.E. (Canadian Acoustics, 1994)
The modern trend to lighter, more flexible floor systems with less damping has resulted in more complaints from walking vibrations. A new design criterion for walking vibration of wide applicability to all floor systems with natural frequencies less than 10 Hz has recently been developed (Allen and Murray, 1993). The new criterion is intended to replace the criterion contained in Appendix G of the CSA Standard CAN/CSA S16.1-M89. Recent experience has shown that the S16.1 criterion has limited application. The new criterion is discussed